What about training? A qualitative study of gamification and AI in training during ERP implementation - Påander,Erik; Risöy Lundberg,Vincent (2025)
Enterprise resource planning (ERP) systems are far reaching within organisations, making ERP implementations highly susceptible to failure. This thesis investigates how change professionals of a large international organisation perceive the role of gamification and artificial intelligence (AI) during ERP implementation and how it can be used to enhance training. While training is widely acknowledged as a critical success factor in ERP rollouts, the study finds that the organisation lacks a coherent training strategy. Using a qualitative and inductive approach grounded in interpretivism and semi-structured interviews, a somewhat decentralised and reactive training environment was revealed. Gamification, although perceived as having great potential, is currently underutilised in the organisation as a method to drive engagement and provide structure. AI, meanwhile, was viewed as a future opportunity to personalise training and aid in the development and understanding of training material. Drawing on ERP training and gamification frameworks, the study highlights the gap between perceived potential and actual implementation, suggesting an integration of gamification to provide structure and strategy in an incoherent training environment.
Keywords: Artificial Intelligence; ERP; Gamification; Implementation; Training